2013
DOI: 10.5713/ajas.2012.12519
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Follicular Dynamics, Ovarian Follicular Growth, Oocyte Yield, <italic>In vitro</italic> Embryo Production and Repeated Oocyte Pick Up in Thai Native Heifers Undergoing Superstimulation

Abstract: The objective of this study was to compare the effectiveness of the protocols for superstimulation of follicular growth in Thai native heifers. Heifers (n = 20) were randomly divided into four groups of five heifers/group. Heifers were given a single dose by i.m. administration of 100 mg Follicle Stimulating Hormone dissolved in polyvinylpyrrolidone (FSHp) at 24 h. Ovum pick up (OPU) occurred at 72 h (F24O72 protocol; Group 1) or 96 h (F24O96 protocol; Group 2), and at 36 h and OPU at 72 h (F36O72 protocol; Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
5
0
2
Order By: Relevance
“…By using various schemes of twice-weekly OPU, less than three COCs from non-stimulated cows were aspirated [ 5 ], but more than nine COCs were recovered from cows that had been stimulated with gonadotropin [ 6 ]. Additionally, compared to continuous OPU sessions, which have been shown to affect the rate of oocyte recovery and the estrous cycle by altering the endocrine function and the mechanisms of follicular growth, leading to irregular estrous intervals [ 7 ] or the absence of estrus [ 5 ], OPU sessions repeated at 3-to-4 day intervals produced a higher recovery rate and produced more COCs [ 8 , 9 ]. Therefore, there is still a need for a new OPU protocol that can support the repeated use of donors for the development of a large number of antral follicles and improve in vitro blastocyst development without altering the ovarian structure or its functions.…”
Section: Introductionmentioning
confidence: 99%
“…By using various schemes of twice-weekly OPU, less than three COCs from non-stimulated cows were aspirated [ 5 ], but more than nine COCs were recovered from cows that had been stimulated with gonadotropin [ 6 ]. Additionally, compared to continuous OPU sessions, which have been shown to affect the rate of oocyte recovery and the estrous cycle by altering the endocrine function and the mechanisms of follicular growth, leading to irregular estrous intervals [ 7 ] or the absence of estrus [ 5 ], OPU sessions repeated at 3-to-4 day intervals produced a higher recovery rate and produced more COCs [ 8 , 9 ]. Therefore, there is still a need for a new OPU protocol that can support the repeated use of donors for the development of a large number of antral follicles and improve in vitro blastocyst development without altering the ovarian structure or its functions.…”
Section: Introductionmentioning
confidence: 99%
“…Follicle stimulating hormone (FSH), exogenous gonadotrophic hormone, is commonly used to stimulate follicular growth, and subsequently obtain a greater number of ovulations, leading to a high number of transferable embryos and a high probability of pregnancy after transfer (Mapletoft, 1986). However, multiple injections of FSH are required due to its short half-life, which is time-consuming and may also be stressful for the cows (Sugano and Shinogi, 1999;Chasombat et al, 2013). Many previous studies proposed solving this issue by administering FSH dissolved in various agents that provide a slow release, such as polyvinylpyrrolidone (PVP) (Yamamoto et al, 1994;Takedomi et al, 1995;Ratsiri et al, 2021) and aluminium hydroxide gel (AH-gel) in cattle (Kimura, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A significant number of reports have characterized these wave patterns in the estrous cycle in European cattle breeds (Bos taurus). Borges et al (2001), Viana et al (2010), and Chasombat et al (2013) reported similar types of wave patterns for Holstein-Zebu crossbred heifers and zebu cows (Bos taurus indicus). Further, the data was confirmed by studies conducted by Zeitoun et al (1996) andD'enjoy et al (2012) that evaluated follicular dynamics in Brahman cows (Bos taurus indicus).…”
Section: Follicular Dynamic Of the Ovaries In The Puerperium Of Dairy Cowsmentioning
confidence: 81%